Variación estacional del uso y preferencia de los tipos vegetacionales por el venado cola blanca en un bosque tropical de Jalisco - Mandujano, Salvador; Gallina, Sonia (Instituto de Ecología, A.C., 2020)
The white-tailed deer (Odocoileus virginianus) inhabits the tropical forest of Chamela in the Pacific coast of thestate of Jalisco, Mexico. In this region the dominant vegetation is the tropical dry forest which settles down in thehills and it is characterized because in the arboreal stratum and understory dominate species that lose its leavesduring six to seven months in the dry season. In contrast, the vegetation that is along the streams and rivers is thetropical semi-evergreen forest in which dominate species with leaves non deciduous. Therefore, in this region aremarkable contrast exists in the food availability, sources of water, covering against the climate and predators.The objective of the present study was to analyze the seasonal variation of the use and the preference that thewhite-tailed deer has for the two main communities in Chamela. The results are discussed in function of twohypothesis which predict bigger preference of the tropical dry forest during the rainy season, and bigger preferenceof the tropical semi-evergreen forest during the dry season. The study was carried out from 1989 to 1993, usingthe methods of direct count of active deer along the year and the count of fecal groups during the dry season. Theunderstory of both plant communities were described for each season of the year quantifying the total number ofarboreal species, shrubs and herbaceous, and it was expressed as density of the number of species for squaremeter; also was estimated the production of biomass to foliage potentially of the parts consumable for the deer likeleaves and tender branches, and it was expressed as gram of dry weight by square meter; finally was estimatedthe relative availability of food in the dry season. As a result it was found that in the rainy season the density ofspecies and the biomass of foliage was bigger in comparison to the dry season (T test of ranges of Mann-Whitney,P <0.01). In particular, in the rainy season the density of species was higher in the tropical dry forest, while in thedry season both the density of species and the biomass was higher in the tropical semi-evergreen (T, P <0.01).They were also significant differences in the density of species and biomass among years (H test of Kruskal-Wallis,P <0.01). Therefore, there was significant positive correlation among the quantity of rain with the density of speciesand biomass to foliage of the species in both types of forests (r², P <0.001). During the dry season the relativeavailability of food was higher in the tropical dry forest than in the tropical semi-evergreen forest (X², P <0.01).Regarding the use of the habitat, higher number of deer was observed during the period of fawning (July toOctober), smaller during the period of mating (November to February), and an increase during the period ofgestation (March to June) (X², P <0.01). The deer used both types of vegetable communities the whole year, butpreferred the tropical dry forest during the rainy season (X², P <0.01) as area of forage, rest and fawning, becauseit offers a higher availability of food of high quality nutritional, and bigger protection against predators. During thedry season the deer not prefer the tropical semi-evergreen forest (X², P> 0.05) nevertheless that this typevegetacional offers higher density of species and biomass in the understory in comparison to the tropical dry forest.This could be due to that the tropical semi-evergreen forest has smaller availability of the plants that consumes thedeer to that the plants probably have a high contained of fiber, and to that has bigger predators presence andhunters. On the contrary, nevertheless the drop density of species and biomass of the plants in the tropical dryforest, the deer used it preferably in the dry time (X², P <0.01) because it has bigger quantity of food, the trees ofthe plum tree (Spondias purpurea) establish mainly in this type of vegetation and its fruits represent a importantresource that provides with water to the deer during this period, the covering of the understory and the topographydiminish the predation risks, and the hillsides with north exhibition have better thermal covering being more humid.Key Words: tropical dry forest, tropical semi-evergreen forest, understory, wet and dry seasons, use-preference,temporal-spatial variation, white-tailed deer, Odocoileus virginianus, Chamela, Mexico.